PEMANFAATAN SUKUK RITEL DALAM PEMBIAYAAN INFRASTRUKTUR PEMBANGUNAN DAERAH KALIMANTAN TIMUR - Binti Nur Asiyah; Dwi Astuti Wahyu Nurhayati; Novi Tri Oktavia; Jamilatun Ni’mah (ITB AAS INDONESIA, 2023)
This research background arises because Local Governor of East Kalimantan is not ready to implement the spirit of decentralization in strengthening the fiscal of local governor to build their own infrastructure. So the infrastructure of area East Kalimantan is not provided maximally to allow the prosperity for the society. Sukuk is one of the alternatives which could be taken by the Local governor to finance the establishing infrastructure of the area of East Kalimantan. This research used descriptive qualitative design to capture the using of sukuk fund in financing the establishing infrastructure of the area in East Kalimantan. The collecting of data was used by the researcher related to the role of sukuk in financing infrastructure of establishing the area of East Kalimantan in the form of secondary data which was relevant with the topic. The result of the study showed that the retail bonds has been used in the area of East Kalimantan in financing of establishing infrastructure of The Kalimantan Institute in 2019, Integrated Laboratory on 2020, The Airport of APT Pranoto from 2020, the infrastructure of State Polytechnic of Balikpapan on 2021, the housing army of TNI AD in 2021, MAN Insan Cendikia Paser from 2018.